Analysis of technical efficiency of dry season rice production in saline and non-saline areas of Bangladesh. (15th August 2022) - Sarker, Jaba Rani; Rolfe, John; Ananda, Jayanath
Abstract: Maintaining productivity and technical efficiency of salinity affected rice farming is essential for food security in Bangladesh, given trends of increasing rates of salinity incursion. Using Bangladesh Integrated Household Survey (BIHS) data, collected by International Food Policy Research Institute (IFPRI), and a translog stochastic production estimation approach, we estimated the differences in technical efficiency between saline and non-saline Boro rice producers. The findings indicate that, although mean efficiency of Boro rice producers in non-saline areas (83%) is higher than that of saline areas (73%), the pooled model suggests that saline farmers are more technically efficient compared with non-saline farmers. Despite this, the per hectare output (productivity) of Boro rice is significantly lower in saline areas (5479.3 kg) compared with non-saline areas (5880.5 kg). Moreover, saline area farmers use more irrigation and family labour to maintain Boro rice output, but more irrigation decreases marginal productivity because of salinity effects. Results also show that there are socio-economic differences between farmers in saline and non-saline areas. The implications of this study are that increased levels of salinity will reduce rice production, as variations in farming systems and technical efficiency are not sufficient to compensate for lost productivity. Highlights: Investigated the technical efficiency differences between saline and non-saline rice production. Saline areas are experiencing lower yield despite being more technically efficient. There is more use of irrigation and family labour in saline areas compared to non-saline areas. Higher irrigation frequency decreases marginal productivity of rice in saline areas. Socio-economic differences have been observed between saline and non-saline areas.